1996
DOI: 10.1111/j.1540-8191.1996.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Coronary Surgery with Thoracoscopic Internal Mammary Artery Dissection: Surgical Technique

Abstract: This new procedure enlarges the field of minimally invasive coronary artery bypass grafting techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…New limited approaches have been introduced as described by Subramanian (4) and Calafwre (5). Furthermore, endoscopically guided techniques as reported by Nataf (6) and Mack (7) can make limited-access surgery easier and so achieve further reduction of invasiveness. During the past two years some of these techniques became standardized and are now widely accepted (8,9,10).…”
Section: Introductionmentioning
confidence: 98%
“…New limited approaches have been introduced as described by Subramanian (4) and Calafwre (5). Furthermore, endoscopically guided techniques as reported by Nataf (6) and Mack (7) can make limited-access surgery easier and so achieve further reduction of invasiveness. During the past two years some of these techniques became standardized and are now widely accepted (8,9,10).…”
Section: Introductionmentioning
confidence: 98%
“…This approach remained mandatory in case of multiple vessels grafting, often by the mean of a left anterior small thoracotomy. ITAs were first dissected using 2D thoracoscopes [5]. The anastomoses were then made under direct view through the thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracoscopic dissection of the internal thoracic artery is technically feasible. 46 Duhaylongsod et al 47 reported the results of harvesting thoracoscopic mammary arteries at three institutions. Of 218 patients, the mammary artery was injured in 4 patients (1.8%), and the procedure was converted to sternotomy in 18 (8%).…”
Section: Other Applicationsmentioning
confidence: 98%